What the Hel: recent advances in understanding rifampicin resistance in bacteria - Sudzinová, Petra; Šanderová, Hana; Koval', Tomáš; Skálová, Tereza; Borah, Nabajyoti; Hnilicová, Jarmila; Kouba, Tomáš; Dohnálek, Jan; Krásný, Libor (FEMS microbiology reviews, 2023)
Rifampicin is a clinically important antibiotic that binds to, and blocks the DNA/RNA channel of bacterial RNA polymerase (RNAP). Stalled, nonfunctional RNAPs can be removed from DNA by HelD proteins; this is important for maintenance of genome integrity. Recently, it was reported that HelD proteins from high G+C Actinobacteria, called HelR, are able to dissociate rifampicin-stalled RNAPs from DNA and provide rifampicin resistance. This is achieved by the ability of HelR proteins to dissociate rifampicin from RNAP. The HelR-mediated mechanism of rifampicin resistance is discussed here, and the roles of HelD/HelR in the transcriptional cycle are outlined. Moreover, the possibility that the structurally similar HelD proteins from low G+C Firmicutes may be also involved in rifampicin resistance is explored. Finally, the discovery of the involvement of HelR in rifampicin resistance provides a blueprint for analogous studies to reveal novel mechanisms of bacterial antibiotic resistance.
Keywords: DNA řízené RNA-polymerasy; Rifampin; rifampin; DNA; antibakteriální látky; Anti-Bacterial Agents; Drug Resistance, Bacterial; Bacteria; DNA-Directed RNA Polymerases; bakteriální léková rezistence